Language policies in education : critical issues - Tollefson, James W. (New York : Routledge, 2013)
"This new edition of takes a fresh look at enduring questions at the heart of fundamental debates about the role of schools in society, the links between education and employment, and conflicts between linguistic minorities and "mainstream" populations"--
Includes bibliographical references and index.
ENH
Keywords: Language and education; Language policy; Language planning; EDUCATION / Educational Policy & Reform / General; EDUCATION / Comparative; FOREIGN LANGUAGE STUDY / English as a Second Language; English language